An Analysis of Character Education Values in English Textbook Entitled “Interactive English” - Miranda, Miranda; Maulina, Maulina; Muflihun, Muflihun (Universitas Pahlawan Tuanku Tambusai, 2025)
Character education holds a significant role in Indonesia's educational framework, particularly within the context of the Merdeka Curriculum. This research explores the extent to which character values are embedded in the Grade VII English textbook entitled Interactive English. Despite the widespread emphasis on character education, its application in instructional materials has not been extensively examined. Employing a qualitative content analysis approach, this study concentrates on the textb.ook’s reading sections and utilizes the 18 character values defined by the Ministry of National Education as an analytical reference. The analysis reveals that, although all character values are intended to be included, their distribution throughout the textbook is inconsistent. Only 14 of the 18 character education values were identified, with “independence” being the most frequently featured. These findings underscore the importance of a more uniform integration of character values in educational content to support national educational objectives. The study suggests that enhancing the design and planning of textbooks is crucial to effectively foster character development alongside language instruction.